Carbon Nanotubes Modified Carbon Cloth Cathode Electrode for Self-Pumping Enzymatic Biofuel Cell - Duong, Ngoc Bich; You, Sheng L.; Huang, Li Z.; Yang, Hsiharng (Journal of Renewable Energy, 2018)
A self-pumping enzymatic biofuel cell (self-pumping EBC) with a new cathodic catalyst which was modified by coating the mixture of carbon nanotubes/caffeic acid (CNTs/CA) on a carbon cloth (CC) to form a CNTs/CA/CC cathode electrode was fabricated. By using UV spectrophotometer, the absorbance of CA, CNTs, and the CNTs/CA composite was observed. To evaluate how the CNTs/CA/CC cathodic electrode improves the electrochemical performance of the self-pumping EBC, the measurement of the redox reaction current peak by cyclic voltammetry (CV) was implemented. In accordance with CV measurement, the utilization of the modified CNTs/CA/CC cathodic electrode exhibited a higher oxygen reduction current peak at 319.1μA under the saturated oxygen. The anode and cathode flow rates were 0.416μls−1 and 0.844 μls−1 which contribute to obtaining the capillary driven liquid efficiency as 30% for the former and 59% for the latter. Moreover, the self-pumping EBC performance tests showed that the maximum power density (MPD) of the self-pumping EBC with the modified cathodic electrode achieved 0.592 mWcm−2 which improved 10% in the performance compared with the bare CC electrode, 0.534 mWcm−2.